Study on the effect of intervention on postpartum psychological improvement and body recovery of caesarean section women based on information‐motivation‐behavioural skills model - Linjun Xu; Li Fang; Qianjuan Xu; Danhong Shen (Wiley, 2023)
Abstract Aim To explore the effect of information‐motivation‐behavioural skills (IMB) model on psychological and emotional state of caesarean section (CS) women. Design Control‐group patients got routine nursing during the preoperative, intraoperative and postoperative periods. Observation‐group patients received routine nursing combined with the IMB model that included specific informational, motivational and behavioural interventions. Methods Pregnant women (n = 102) who underwent CS in Hangzhou Women's Hospital were randomly divided into Control and Observation‐groups (n = 51 each). Self‐rating anxiety scale (SAS), self‐rating depression scale (SDS) and general self‐efficacy scale (GSES) scores, complication rate, fatigue severity scale (FSS) and Edinburgh postpartum depression scale (EPDS) scores were compared. Result Interventions lowered SAS and SDS scores, significantly lower in the Observation‐group (p < 0.05), and increased GSES scores, significantly higher in the Observation‐group (p < 0.05). Observation‐group had less complications (4.08% vs. 17.39% in the Control‐group; p < 0.05), and decreased FSS and EPDS scores (p < 0.05).